Republic of Mozambique : Staff Report for the 2011 Article IV Consultation, Second Review Under the Policy Support Instrument, and Request for Modification of Assessment Criteria; Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Mozambique. (IMF Staff Country Reports; Country Report, 2011)
In this paper, Mozambique's financial stability is discussed. The poverty reduction strategy (PARP) aims to respond to these challenges and create the conditions for high, sustained, and inclusive economic growth. The prudent policies resulted in strong economic performance. Executive Directors emphasized the importance of adhering to a prudent borrowing strategy, further strengthening debt management, and improving investment planning. The resilience of the banking system during the global crisis has been noted; and continued vigilance was recommended in light of remaining vulnerabilities.